(untitled) (Raparin Journal of Humanities (RJH), 2025)
The research which is entitled (A Comparison Study of Kurdish Language Alphabet with reference to the Kurdistan Newspaper and the Current Form of Kurdish Language) compares between the first issue of Kurdistan newspaper with the current writing alphabet of Kurdish language, for example, Kurdish Academy alphabet. The study discusses the role of the Kurdish alphabet in the field of journalism. Including the writing alphabet system, Kurdistan newspaper alphabet has been presented in this period and questions such as how writing system was and what kind of alphabetic system was used have been shown. Although the alphabet is the same as the current Kurdish alphabet, there are many differences, which are due to the influence of foreign languages, especially Arabic. Kurdistan newspaper is the first step in academic writing in Kurdish journalism, but it has not been freed from the influence of the Arabic alphabet. The alphabet used to write the Kurdistan newspaper was dominated by Arabic on the one hand, and on the other hand, as it is important to note that Kurdistan newspaper made use of the Arabic alphabet to fill the gaps in the Kurdish alphabet at that time. It used the Arabic letters in a way that influenced the rules of the Kurdish language, thus, producing a codified writing that was an important turning point in the Kurdish language at that time. The paper consists of two parts: practical, theory, conclusions, list of sources and appendix: Section one consists of five topics: - The first topic is the concept and definition of the alphabet, the second topic is the alphabet related to the ethnicity of the language, the third topic is the history of the Kurdish alphabet. Section two consists of six topics: - The first topic is a brief history of Kurdistan newspaper, the second topic is the time and place of publication, printing house, owner and editor of Kurdistan newspaper, the third topic is the role of Kurdish language in Kurdistan newspaper Kurdish in Kurdistan newspaper. The sixth topic is the letters that are not in Kurdish.